1998
DOI: 10.1145/301589.286868
|View full text |Cite
|
Sign up to set email alerts
|

Comparing mostly-copying and mark-sweep conservative collection

Abstract: Many high-level language compilers generate C code and then invoke a C compiler for code generation. To date, most of these compilers link the resulting code against a conservative mark-sweep garbage collector in order to reclaim unused memory. We i n troduce a new collector, MCC, based on an extension of mostly-copying collection. We analyze the various design decisions made in MCC and provide a performance comparison to the most widely used conservative mark-sweep collector the Boehm-Demers-Weiser collector.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Other studies have identified similar opportunities Zorn, 1990;Smith and Morrisett, 1998). IBM's Persistent Reusable JVM attempts to split the heap into multiple parts grouped by their expected lifetimes, employs heap-specific GC models and heap-expansion to avoid GCs.…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies have identified similar opportunities Zorn, 1990;Smith and Morrisett, 1998). IBM's Persistent Reusable JVM attempts to split the heap into multiple parts grouped by their expected lifetimes, employs heap-specific GC models and heap-expansion to avoid GCs.…”
Section: Related Workmentioning
confidence: 98%
“…The goal of most of this prior work has been to provide general-purpose mechanisms that enable high performance execution across all applications. However, many researchers, including ourselves, find that the performance of a memory management system (the allocator and the garbage collector) is dependent upon application behavior and available resources (Soman et al, 2004;Attanasio et al, 2001;Fitzgerald and Tarditi, 2000;Zorn, 1990;Smith and Morrisett, 1998). That is, no single collection system enables the best performance for all applications and all heap sizes and the difference in performance can be significant.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously supporting ambiguous roots and heap compaction is only one way that mostly copying collection can balance the tradeoffs of copying and noncopying collection: there are other opportunities to use inplace promotion. In particular, it is well-recognized [26] that there is little or no benefit in copying objects that consume all of the space associated with a page. These large objects are expensive to copy, both in terms of the time required to do so and the additional space required for the duplicate.…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…Previous implementations of mostly copying collection [3,26] promoted pages only in the presence of ambiguous roots or large objects. We extend this work and use page residency, the density of reachable objects on a page, to determine when to promote or evacuate the objects on a given page.…”
Section: Page Residencymentioning
confidence: 99%
See 1 more Smart Citation